Development and characterization of carrageenan/nanocellulose/silver nanoparticles bionanocomposite film from Kappaphycus alvarezii seaweed for food packaging - Syafiqah Syazwani Jaffar; Suryani Saallah; Mailin Misson; Shafiquzzaman Siddiquee; Jumardi Roslan; Wuled Lenggoro (Elsevier, 2025)
This study focuses on developing seaweed-based bionanocomposite films using carrageenan (Cr) as the matrix with nanocellulose (NC) as reinforcing material and silver nanoparticles (AgNPs) as antimicrobial agent, all sourced from Kappaphycus alvarezii seaweed. The Cr/NC/AgNPs bionanocomposite films were created using a solvent casting technique and comprehensively characterized to assess their suitability for food packaging applications. The addition of NC and AgNPs significantly improved the mechanical properties, with a maximum load of 16.73 N, tensile strength of 6.81 MPa, elastic modulus of 32.18 MPa, and elongation at break of 18.73 %. The films exhibited excellent optical properties and enhanced moisture barrier performance, with a water vapor transmission rate of 5.62 g/m2d, moisture content of 11.09 %, moisture uptake of 85.98 %, and water solubility of 47.7 %. Thermal analysis showed improved stability, with decomposition temperatures up to 282 °C. The films biodegraded completely within 15 days. Storage tests on bread as a food model demonstrated the films' antimicrobial efficacy, preventing mold growth for one month. Silver ion migration (0.013 μg/g) was well below the safety limit (0.05 μg/g). These results highlight the potential of Cr/NC/AgNPs bionanocomposite films as sustainable, functional materials for food packaging.